The morbidity and cost of vocal cord dysfunction misdiagnosed as asthma - Traister, Russell S; Fajt, Merritt L; Petrov, Andrej A (Allergy and asthma proceedings, 2016)
Vocal cord dysfunction (VCD) is frequently misdiagnosed and mistreated as asthma, which leads to morbidity secondary to unnecessary medication use and increased health care utilization. We identified discriminating symptoms and triggers, and analyzed the costs, morbidity, and health care burden associated with misdiagnosis of VCD as asthma. We sought to determine if current measures of asthma control contributed to these findings. We evaluated if a simple set of breathing exercises would be an effective low-cost treatment option for those with VCD. We compared the demographics, comorbidities, clinical symptoms, and symptom triggers of subjects with VCD misdiagnosed as asthma compared with those not misdiagnosed as asthma. Costs secondary to asthma misdiagnosis were quantified, and the effectiveness of breathing exercises as a treatment option was evaluated. We identified symptoms of shortness of breath, wheezing, chest tightness, and a trigger of exercise as being more common in the subjects with VCD misdiagnosed as asthma. Asthma medication use and health care utilization and costs were also higher in this group. The subjects with VCD had Asthma Control Questionnaire scores that labelled them as having uncontrolled asthma. Breathing exercises appeared to offer an inexpensive and effective treatment option for subjects with VCD. Misdiagnosis of VCD as asthma leads to significant morbidity and increased costs, and misuse of measures of asthma control may be contributing to these findings. Timely and accurate diagnosis of VCD and the use of breathing exercises have the potential to eliminate or minimize the burdens on the patient and the health care system.